Hyperbeanols F-Q, diverse monoterpenoid polyprenylated acylphloroglucinols from the flowers of Hypericum beanii. (March 2019) - Li, Yi-Ran; Xu, Wen-Jun; Wei, Shan-Shan; Lu, Wei-Jia; Luo, Jun; Kong, Ling-Yi
Abstract: Hyperbeanols F-Q, which are twelve undescribed monoterpenoid polyprenylated acylphloroglucinols, and four known analogues were isolated from the dried flowers of Hypericum beanii . Their structures were elucidated by detailed HRESIMS and 1D and 2D NMR data analyses. The absolute configurations of hyperbeanols FH were established by the circular dichroism (CD) exciton chirality method. The plausible biosynthetic pathway speculation of hyperbeanols F-Q indicated that diverse reactions, including prenylation, 1, 6-ene reaction, rearrangement, epoxidation and dehydration, contributed to their diverse skeletons. Hyperbeanols FI, O and hypercalin B exhibited moderate nitric oxide (NO) inhibitory activities in LPS-induced RAW 264.7 macrophages, with IC50 values in the range of 17.11–28.74  μ M. Graphical abstract: Twelve undescribed monoterpenoid polyprenylated acylphloroglucinols with diverse structures were isolated from the flowers of Hypericum beanii . Highlights: Twelve undescribed monoterpenoid PPAPs were isolated from Hypericum beanii. Absolute configurations of1 –3 were assigned by CD exciton chirality method. Selected compounds exhibited moderate anti-inflammatory activities.